Rectification ratio and direction controlled by temperature in copper phthalocyanine ensemble molecular diodes - Sergi Lopes, Carolina; Merces, Leandro; de Oliveira, Rafael Furlan; de Camargo, Davi Henrique Starnini; Bof Bufon, Carlos César (Royal Society of Chemistry (RSC), 2020)
Organic diodes and molecular rectifiers are fundamental electronic devices that share one common feature: current rectification ability. Since both present distinct spatial dimensions and working principles, the rectification of organic diodes is usually achieved by interface engineering, while changes in molecular structures commonly control the molecular rectifiers' features. Here, we report on the first observation of temperature-driven inversion of the rectification direction (IRD) in ensemble molecular diodes (EMDs) prepared in a vertical stack configuration. The EMDs are composed of 20 nm thick molecular ensembles of copper phthalocyanine in close contact with one of its fluorinated derivatives. The material interface was found to be responsible for modifying the junction's conduction mechanisms from nearly activationless transport to Poole-Frenkel emission and phonon-assisted tunneling. In this context, the current rectification was found to be dependent on the interplay of such distinct charge transport mechanisms. The temperature has played a crucial role in each charge transport transition, which we have investigated via electrical measurements and band diagram analysis, thus providing the fundamentals on the IRD occurrence. Our findings represent an important step towards simple and rational control of rectification in carbon-based electronic nanodevices.